Barriers to effective uptake of malaria prevention interventions in Ibadan, South West Nigeria: a qualitative study - Oladimeji, Kelechi Elizabeth; Tsoka-Gwegweni, Joyce Mahlako; Gengiah, Santhanalakshmi; Daftary, Amrita; Naidoo, Kogieleum (International Journal Of Community Medicine And Public Health, 2018)
Background: Although control measures have achieved considerable success, malaria is still a major public health problem in Nigeria and sub-Saharan Africa. The malaria burden is more among vulnerable groups like pregnant women and under-five aged children. This study explored barriers affecting uptake of current malaria prevention interventions in Ibadan, Southwest Nigeria. Methods: The study was conducted using qualitative research methods between May and August 2016 among community residents in Ibadan, Oyo state-Nigeria. Six focus group discussions (FGDs) and 16 in-depth interviews (IDI) were conducted with community members who were purposively selected and consented to participate in the study. The participants were grouped into six homogenous focus groups which included; pregnant women, mothers of under-five children, husbands, fathers, civil society members, and health staff such as hospital manager, nurses, pharmacist, medicine vendors, doctors, state program staff and national program staff. Data were transcribed, manually coded and analysed using content and thematic method. The Biomedical Research Ethics Committee (BREC), University of KwaZulu-Natal, South Africa and Oyo state Ministry of Health Ethics Committee, Nigeria both approved the study. Results: Knowledge on malaria causality and symptoms, prevention strategies, beliefs, fear of side effects from current malaria preventive measures, corruption and difficulty in obtaining nets, and poor environmental hygiene were some of the themes which emerged as barriers to the effective uptake of malaria prevention intervention. Conclusions: Strategies at the community level are urgently needed to address and improve within socio-cultural context uptake of current malaria prevention interventions.